Essence and structure of the readiness of future primary school teachers to design the learning environment - Oleksenko, K.; Khavina, I. V. (Universidad del Zulia, Maracaibo, Venezuela, 2021)
The purpose of the study is to determine the essence of the preparation of future primary school teachers to design the learning environment in the operation of the new Ukrainian school. The application of methods that helped to carry out theoretical research: analysis and synthesis, systematization of materials, historical and logical, comparative, systemic and structural, allowed to study the essence of the preparation of future primary school teachers to design the learning environment in the New Ukraine School. This study allowed us to determine the essence of the preparation of future primary school teachers as specialists of the new generation, to design the learning environment of primary school students. The preparation structure of future primary school teachers is determined to design the learning environment and the content of its main constructs is specified, namely: the motivational, cognitive, operational-active and emotional-volitional components.
Keywords: primary school; design; learning environment; teacher attitudes